2014
DOI: 10.4081/jlimnol.2014.935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating macroinvertebrate community shifts in the confluence of freestone and limestone streams

Abstract: Aquatic macroinvertebrates are critical to ecosystem functioning through their regulation of many essential top-down and bottom-up ecosystem processes such as energy translocation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Large confluence ratios were associated with larger differences in communities. This observation concurs with Rice et al () and the work of others focused at smaller spatial scales (Hellmann et al, ; Kiffney et al, ; Milesi & Melo, ; Perry & Schaeffer, ). Similarly, the TITAN analysis showed support for a threshold at the GH confluence where the river increases size from 72 to 118 km 2 with a CSR of 0.64.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Large confluence ratios were associated with larger differences in communities. This observation concurs with Rice et al () and the work of others focused at smaller spatial scales (Hellmann et al, ; Kiffney et al, ; Milesi & Melo, ; Perry & Schaeffer, ). Similarly, the TITAN analysis showed support for a threshold at the GH confluence where the river increases size from 72 to 118 km 2 with a CSR of 0.64.…”
Section: Discussionsupporting
confidence: 92%
“…Research on the influence of tributaries on network patterns has largely focused on localized small‐scale changes in mainstem river characteristics at the point where tributaries join mainstem rivers (Bruns et al, ; Clay, Muehlbauer, & Doyle, ; Hellmann, Erikson, & Queenborough, ; Kiffney, Greene, Hall, & Davies, ; Milesi & Melo, ; Perry & Schaeffer, ; but see Rice et al, ). The probability of a significant confluence effect is a function of tributary size relative to the mainstem river (confluence symmetry ratio [CSR]; Benda, Poff, et al, ; Rice, ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting stream types merging at confluences have the potential to create ecotones and these heterogeneous junctures are often hot spots for local scale α biodiversity (Osborne and Wiley 1992;Kiffney et al 2006;Milesi et al 2014;Hellmann et al 2015). Increasing to the basin scale, Finn et al (2011) documented that among site β biodiversity of benthic invertebrates was much greater among headwater than in mid-order streams at both population-genetic and community levels.…”
Section: R a F Tmentioning
confidence: 99%
“…It’s development and use would support further research of the ecology of stream confluences. Some examples include effects related to: (1) geographic differences (e.g., Benda, Andras, et al 2004); (2) urbanization and other land cover changes; (3) differences between mainstem and tributary channel gradients; (4) position in the stream network (e.g., Grenouillet et al 2004; Thornbrugh and Gido 2010); (5) influence of lithology (Hellman et al 2015); (6) influences of stressors and disturbance (e.g., Katano et al 2009; Boddy et al 2019); (7) influence of soil differences, and; (8) interaction between tributary size (discharge) and differences in mainstem and tributary watershed characteristics (e.g., Jones and Schmidt 2017). Some of the aforementioned topical examples have not been studied to our knowledge (Table 1), such as land cover change, and complementary studies for topics reported in the literature would likely help to advance a nascent field (Rice et al 2008; Jones and Schmidt 2017).…”
Section: Introductionmentioning
confidence: 99%